- Thread starter
- #1

#### karush

##### Well-known member

- Jan 31, 2012

- 2,886

Convert the differential equation

$$\displaystyle y^{\prime\prime} + 5y^\prime + 6y =0$$

ok I presume this means to find a general solution so

$$\lambda^2+5\lambda+6=(\lambda+3)(\lambda+2)=0$$

then the roots are

$$-3,-2$$

thus solutions

$$e^{-3x},e^{-2x}$$

ok I think the Wronskain matrix is next which I have never done.

well so far,,,, any suggest...

also this might be DE question ... not sure..

$$\displaystyle y^{\prime\prime} + 5y^\prime + 6y =0$$

ok I presume this means to find a general solution so

$$\lambda^2+5\lambda+6=(\lambda+3)(\lambda+2)=0$$

then the roots are

$$-3,-2$$

thus solutions

$$e^{-3x},e^{-2x}$$

ok I think the Wronskain matrix is next which I have never done.

well so far,,,, any suggest...

also this might be DE question ... not sure..

Last edited: